Answer:
3 7/50
Step-by-step explanation:
so you need them to become common denominators
a common multiple they both have would be is 77
6/7 becomes 66/77 and 3/11 becomes 21/77
now we divide
keep the 66/77 as is and flip 21/77 (keep, change, flip)
so now our equation looks like this: 66/77 x 77/21
and your answer is 3.14
but as a fraction it is 157/50 and to simplified it would be 3 7/50 (mixed fraction)
Step-by-step explanation:
I am not sure what your problem here is.
you understand the inequality signs ?
anyway, to get
6×f(-2) + 3×g(1)
we can calculate every part of the expression separately, and then combine all the results into one final result.
f(-2)
we look at the definition.
into what category is -2 falling ? the one with x<-2, or the one with x>=-2 ?
is -2 < -2 ? no.
is -2 >= -2 ? yes, because -2 = -2. therefore, it is also >= -2.
so, we have to use
1/3 x³
for x = -2 that is
1/3 × (-2)³ = 1/3 × -8 = -8/3
g(1)
again, we look at the definition.
into what category is 1 falling ? the one with x > 2 ? or the one with x <= 1 ?
is 1 > 2 ? no.
is 1 <= 1 ? yes, because 1=1. therefore it is also <= 1.
so we have to use
2×|x - 1| + 3
for x = 1 we get
2×0 + 3 = 3
6×f(-2) = 6 × -8/3 = 2× -8 = -16
3×g(1) = 3× 3 = 9
and so in total we get
6×f(-2) + 3×g(1) = -16 + 9 = -7
P
pp is an exponential function with an initial value of
Answer:
163216
Step-by-step explanation:
If it's the sign of multiplication
404/4=101
2*2=4*101=404^2=163216
or,
If it's x
(404/4)x(2x2)
(101)x(2x2)
101x (4x)^2
1616x^2
2611456
I am not sure if it's right
Answer:
hii
Step-by-step explanation: